PENGARUH EDUKASI DENGAN MEDIA E-BOOKLET TERHADAP PENGETAHUANiIBU TENTANG STUNTING DI DESA PANGAUBAN WILAYAH KERJA PUSKESMAS BATUJAJAR TAHUN 2024: The Influence Of Education With E-Booklet Media On Mother's Knowledge About Stunting At Pangauban Village Batujajar Health Center Working Area 2024 - Savitri, Rahayu; Maryati, Sri; Rianto, Budi; Yupira, Palpi (LPPM - STIKES Pemkab Jombang, 2024)
Stunting is one of the problems faced in the world, especially in developing countries which have middle to lower average incomes. Based on data obtained from the West Bandung District Health Service, the prevalence of stunted toddlers reached 5.16% August (2023), this is due to several factors causing stunting, one of which is a lack of maternal knowledge which influences the incidence of stunting. The efforts to minimize the number of stunting incidents include providing education using e-booklet media. The aim of the study was to determine the influence of education using e-booklets on mothers' knowledge about stunting. This study method is pre-experimental with a one group pretest-posttest design. The population of this study was all mothers with toddlers in Pangauban Village, namely 1,520 mothers, and the sample size was 20 mothers of toddlers using a non-probability sampling technique. Data analysis uses the Dependent T-Test (Paired Samples Test). The results of this study showed that the average knowledge value of mothers before being given education using e-booklets was 68.45 and after being given education using e-booklets was 76.60, with ?-Value = 0.006, which means there was an influence of education using e-booklet media on mother’s knowledge about stunting. It is hoped that the E-Booklet can be used as a media for providing health education in order to minimize the occurrence of stunting.